Analysis of reactive phosphorus treatment by filter materials at the edge of tile-drained agricultural catchments: A global view of the current status and challenges. (15th December 2022) - Mendes, Lipe R.D.; Pugliese, Lorenzo; Canga, Eriona; Wu, Shubiao; Heckrath, Goswin J.
Abstract: Phosphorus losses from agriculture have long generated concern due to the ecological impact on surface waters. Here tile-drained agricultural catchments are a critical source for concentrating and transporting phosphorus bioavailable forms or dissolved reactive phosphorus (DRP). Hence, edge-of-field technologies have been introduced to reduce DRP loads. Filter systems have received special attention due to their targeted approach using a permeable filter material (FM) rich in DRP sorbents. This review explores the performance and applicability of FMs in the aforementioned context because of the growing number of studies. An overall analysis revealed that sorption is preferable to precipitation for DRP retention at the edge-of-field, and that FM pH and particle size affect sorption properties and subsequently DRP retention and lifetime. Thus, FMs with predominant amounts of iron and/or aluminium can be recommended. Such materials generally have an appreciable availability of DRP binding sites, strong bonds with DRP and short reaction times, as well as low desorption, which lead to good operation. On the other hand, FMs with predominant amounts of calcium and/or magnesium are restricted to catchments with favourable conditions unless they have optimal reactivity for DRP. The review also found that hydraulic retention time plays a key role in the performance and applicability of FMs, especially in those dependent on precipitation reactions. Therefore, it is crucial that FMs are designed, constructed and managed according to the catchment conditions—including normally varying flow rates and DRP concentrations—in order to ensure successful operation. This reflects in long-term, high and steady net DRP retention along with low costs, thus improving the FM cost-effectiveness, besides discharging non-harmful effluents to aquatic ecosystems. Graphical abstract: Image 1 Highlights: Filter systems can reduce the load of reactive phosphorus in tile drainage water. Iron-based materials ensure good reactive phosphorus retention through sorption. Use of calcium-based materials is restricted to favourable conditions. Performance is affected by the reactivity for phosphorus or sorption properties. Hydraulic retention time plays a key role in performance and applicability.